Šorli, Albreht, Nietzsche - Kos, Matevž (Jezik in slovstvo, 2001)
The article discusses echoes of Nietzsche's philosophy in literary works by Ivo Šorli and Fran Albreht, more spcifically in Šorli´s short story Hic Rhodus! (1902-1903) and his novel Človek in pol (Nam and a Half, 1903) and Fran Albreht's collection of poems Mysteria dolorosa (1917).
Keywords: Šorli, Ivo, 1877-1958; Albreht, Fran, 1889-1963; Nietzsche, Friedrich, 1844-1900; Slovene literature; slovenska književnost; Albreht, Fran: Mysteria dolorosa; Šorli, Ivo: Hic Rhodus!; Šorli, Ivo: Človek in pol; literarne študije; ničejanstvo; nemška filozofija